Design system for normalization by Using Normal Forms - Elham hassan Aziz (Tikrit Journal of Pure Science)
Electronic learning is the use of modern technology of different  types for information delivery in order to reduce both time and effort for maintaining a wide range of benefit through many patterns or programs like simulation which help the learner to facilitate his opportunities for  learning and ensuring  leaner a attention and follow up . Simulation help for adapting an interaction environment which gives alive experiment that can not  be obtained from books or teacher unless using computer .